Effectiveness of the relationship marketing in Malaysian Cocoa Board (MCB) toward clients satisfaction / Nuur Fasihah Afiqah Ismail - Ismail, Nuur Fasihah Afiqah (2013)
Malaysian Cocoa Board (MCB) is one of government body who practiced the Relationship Marketing in their business performance which is relationship marketing (RM) as one of the key functionality in enhancing business performance. RM is defined as the identification, establishment, maintenance, enhancement, modification and termination of relationships with clients to create value for customers and profit for organization by a series of relational exchanges that have both a history and a future. This paper examines the effectiveness of relationship marketing strategies used by Malaysian Cocoa Board (MCB), The primary objective of the study was to determine either the relationship marketing strategy that used by MCB is effective enough in order to satisfied clients. Other that that, if the relationship marketing strategy that practiced is not effective they attempt to find out the solution on how to improve it well for the future performance of MCB. The effectiveness of the relationship marketing strategy that practiced by MCB will be identified through the process of analyzing the final data collected from the questionnaire. The total of respondent will be fairly sufficient in order to increase the accuracy of the research. Other than that, the recommendation from respondents and also researcher will be figured out soon after the final analysis has been obtained.